A Conceptual Framework for the Impact of Obesity on Risk of Cesarean Delivery. Issue 3 (September 2019) - Rogers, A.; Harper, L.; Mari, G.
Abstract : ( Am J Obstet Gynecol . 2018:219:356–363) In the United States in 2014, cesarean deliveries (CD) accounted for 32.3% of the nearly 4 million births. A third of reproductive-age women are obese. When compared with normal-weight women, obese women who delivered via CD had an increased risk of venous thromboembolism, infection, blood transfusion, and maternal mortality. The mechanisms through which obesity increases risk for CD are poorly understood. This study presented a conceptual framework that hypothesized how obesity may impact factors that would lead to a CD.